2003
DOI: 10.1007/s11745-003-1111-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CLA isomer distribution of cow's milk lipids

Abstract: The uniqueness of ruminant milk lipids is based on their high concentration of CLA. Maximal CLA concentrations in milk lipids require optimal conditions of ruminal fermentation and substrate availability, conditions like those present in pasture-fed cows. Our previous work showed that farm management (indoor feeding vs. pasture feeding) markedly influenced the CLA concentration. In this study, the objective was to evaluate the influence of the farm management system as dependent on different locations. Milk sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
169
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(205 citation statements)
references
References 41 publications
28
169
1
7
Order By: Relevance
“…The higher level of total PUFAs in the F x J in this study agrees with results obtained in other studies. Parodi (1999) noted higher levels of PUFAs with cows on pastures, with a similar tendency shown by Grega et al (2005) and Kraft et al (2003 found similar results, although their study focused on comparing beef breeds, Montbéliarde and Czech Fleckvieh. Total CLA was higher (P <0.05) in the milk of F x J in comparison with Jersey cows.…”
Section: Resultssupporting
confidence: 55%
“…The higher level of total PUFAs in the F x J in this study agrees with results obtained in other studies. Parodi (1999) noted higher levels of PUFAs with cows on pastures, with a similar tendency shown by Grega et al (2005) and Kraft et al (2003 found similar results, although their study focused on comparing beef breeds, Montbéliarde and Czech Fleckvieh. Total CLA was higher (P <0.05) in the milk of F x J in comparison with Jersey cows.…”
Section: Resultssupporting
confidence: 55%
“…Since n-6 PUFA in the hay-alone groups were reduced, the proportion of n-6 to n-3 was clearly less than half of that found in group LC. This shows that the omission of C18:1 and C18:2 input from maize and cereals and of protected SFA from the concentrates may already explain a part of the differences in fatty acid profi le of cow's milk found between lowland and alpine systems (Kraft et al, 2003). Feeding of the alpine hay, representing a typical alpine forage quality (Leiber et al, 2004a), reduced milk fat proportions of C6:0 to C14:0 (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Milk products originating from high alpine grazing of cows seem to provide an extraordinarily high proportion of t9c11-conjugated linoleic acid (CLA) and n-3 polyunsaturated fatty acids (PUFA; Kraft et al, 2003) making these products functional feeds with an expected high value for human health (Hauswirth et al, 2004). However, the question remains open whether a comparable fatty acid profi le can be achieved under defi ned environmental and feeding conditions in lowlands (Leiber et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…The t7,c9 CLA isomer is also derived almost exclusively from endogenous synthesis via the D9-desaturase using rumen t7-18:1 as a substrate (which explains its classical second position among CLA isomers), whereas the other CLA isomers are produced in the rumen (Piperova et al, 2002;. Interestingly enough, t11,c13-CLA is also the second most important CLA in milk fat from cows grazing mountain pasture, which is rich in 18:3n-3 (Kraft et al, 2003;Collomb et al, 2004) and in milk fat from cows receiving hay and linseed oil (Roy et al, 2006). Moreover, a high correlation was found between the intake of 18:3n-3 and t11,c13-CLA (Collomb et al, 2004).…”
Section: Discussionmentioning
confidence: 99%